Measurement of LDL-C after treatment with the CETP inhibitor anacetrapib - Davidson, Michael (The American Society for Biochemistry and Molecular Biology, 2013)
Estimation of low-density lipoprotein cholesterol (LDL-C) using the Friedewald (FR) formula is often inaccurate when triglycerides are elevated or VLDL particle composition is altered. We hypothesized that LDL-C estimation by the FR formula and other measurement methods might also be inaccurate in individuals treated with a cholesteryl ester transfer protein (CETP) inhibitor. An assay comparison study was conducted using pre and posttreatment serum samples from 280 of the 811 patients treated with the CETP inhibitor anacetrapib in the DEFINE study (determining the ef ficacy and tolerability of CETP in hibition with anac e trapib). After 24 weeks of treatment with anacetrapib, mean LDL-C values by FR formula, Roche direct method (RDM) and Genzyme direct method (GDM) deviated from that measured by the β-quantification (BQ) reference method by –12.2 ± 7.5, –10.2 ± 6.6, –10.8 ± 8.8 mg/dl, respectively. After treatment with anacetrapib, the FR formula and detergent-based direct methods provided lower LDL-C values than those obtained by the BQ reference method. The bias by the FR formula appeared to be due to an overestimation of VLDL-C by the TG/5 component of the formula. Evaluation of the clinical significance of these findings awaits comprehensive lipid and cardiovascular outcome data from ongoing Phase III clinical studies of anacetrapib.